Production of biodiesel from jatropha c. oil using koh and lipase candida r. in an airlift reactor - Liyana, Amer Shah (2010)
Biodiesel was one of the alternatives fuels to fuel the vehicle since world petroleum depleted. Production of biodiesel from jatropha oil was attractive option compared to other edible oil such canola oil because it has no competed with food consumption issue. This research objective was to produce biodiesel from Jatropha Curcas L. using KOH and Lipase Candida Rugosa catalyst and to investigate the effect of reaction time, reaction temperature and methanol/oil ratio to biodiesel production. Two-stage transesterification method was used for KOH catalyst reaction while onestage transesterification for biocatalyst reaction. Two-stage transesterfication method was the suitable method used to reduce high free fatty acid content in jatropha oil and increase the biodiesel yield. Without acid treatment in two-stage transesterification process, triglycerides tend to go through saponification reaction which produce soap rather than biodiesel. Methanol was used as solvent in both methods due to it short chain characteristic that can produce higher result than other type of alcohol. As a conclusion, biodiesel has been successfully produced from jatropha oil using KOH and Lipase Candida Rugosa enzyme and resulted 98% and 4% biodiesel yield respectively. The highest biodiesel production was obtained at 65°C at 1 hour of reaction and 6:1 methanol/oil ratio.